KINETI-KIDS a fitness program for schoolchildren: the physical activity component (2008)
This study is one of the components of the "Kineti-Kids" a fitness program for school children. This physical activity component assessed the physical activity levels by period, by gender, and by type of school, among elementary school children from grades one to six, using a structured questionnaire. It also aimed to determine the outcome or effectiveness of the intervention program in terms of physical activity levels from baseline to the end line of the study. Findings of the study could provide a baseline data on the physical activity levels among elementary schoolchildren and an important step in establishing a benchmark from which changes in the physical activity levels could be measured. A physical activity questionnaire was administered among the school children to determine change in the level of physical activity as a result of the program. The questionnaire assessed the levels of physical activity (less active, moderate and active) on a Physical Education (P.E.) day, non-P.E. day, and a weekend. A scoring system was used to determine the physical activity levels. Results revealed a positive outcome of an intervention program. Slight inconsistencies were observed between periods of observation (baselineYr1, midlineYr1, endlineYr1, baselineYr2 and endline Yr2), but positive changes were still seen in all grade levels. The number of less active children decreased from baseline until the end of the study and a modest increase in the percentage of moderately active and active children were seen. Thus, for changes to be effected on the physical activities of children, a longer period f intervention and changes or additions to the curriculum should be done. Future research may also be better served by examining the patterns of involvement in the physical activity of the schoolchildren and the casual factors behind the results of the pattern to further our understanding of results.
Keywords: Physical fitness for children